Ekstraksi DNA Pseudomonas aeruginosa: Komparasi Metode NaOH, Perebusan, Iradiasi Microwave, dan Kit Komersial. - Prayogo, Fitra Adi; Chakim, Irfanul (Soegijapranata Catholic University, 2025)
This study aims to compare the effectiveness of four methods of DNA extraction from Pseudomonas aeruginosa bacteria: NaOH, boiling, microwave, and a commercial kit. The four methods were evaluated based on DNA quantity and quality, as well as time and cost efficiency. Results showed that the microwave method yielded the highest DNA concentration (92.23 ± 1.04 ng/µL) with optimal purity (A260/A280 ratio of about 1.82). The boiling method had the highest purity ratio (1.90 ± 0.05), but failed to produce PCR amplification despite its high concentration. The commercial kit produced the best quality DNA but with the lowest concentration (14.35 ± 0.74 ng/µL) and highest cost (IDR 50,000.00 per sample). In terms of efficiency, the microwave and boiling methods were the most cost (IDR 500.00 per sample) and time (less than 15 minutes) efficient. Based on the total analysis, the microwave method offers the best balance between quality, quantity, time, and cost, so it is recommended as an efficient alternative for research and diagnostic applications, especially in microbiological surveillance or epidemiological studies. However, for sensitive downstream applications such as genome sequencing, the use of commercial kits remains safer despite the high cost.